2017
DOI: 10.7324/rjc.2017.1031766
|View full text |Cite
|
Sign up to set email alerts
|

CHARACTERIZATION, ANTIBACTERIAL AND ANTIOXIDANT ACTIVITY OF MANGOSTEEN (Garcinia Mangostana L.) PERICARP NANOSIZED EXTRACT

Abstract: The difference of crude size was reported to give impact over magosteen pericarp nanosized extract (ME) antibacterial and antioxidant activity. Nano-sized ME (213,6 nm) showed the best antibacterial activity in inhibiting the growth of bacteria compared to extract from crude with a particle size of 20 mesh and 40 mesh. In the other hand, its antioxidant activity was the lowest. Meanwhile, the chemical compound contained in the ME supposed to support both activities. This research was conducted to characterize … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Free radical scavenging activity was determined using DPPH method [12][13][14] . Gallic acid, which is known to have a strong antioxidant activity, was used as reference standard.…”
Section: Free Radical Scavenging Activitymentioning
confidence: 99%
“…Free radical scavenging activity was determined using DPPH method [12][13][14] . Gallic acid, which is known to have a strong antioxidant activity, was used as reference standard.…”
Section: Free Radical Scavenging Activitymentioning
confidence: 99%
“…Lalitha et al (2017) showed that ethyl acetate extract of mangosteen leaf was able to inhibit the growth of various bacteria ( Staphylococcus epidermidis , Staphylococcus aureus , Micrococcus luteus , Enterobacter aerogenes , Escherichia coli , Vibrio parahaemolyticus , Proteus vulgaris , Klebsiella pneumoniae , Yersinia enterocolitica, and Salmonella typhimurium ) and fungi ( Trichophyton mentagrophytes 66/01 and T. rubrum 57/01). Nanosized mangosteen pericarp extract has also been shown to possess anti-bacterial properties against Staphylococcus aureus , Bacillus cereus and Shigella flexneri (Sugita et al, 2017). Furthermore, both water (1 mg/mL) and methanol (8.75 μg/mL) extracts of mangosteen pericarp were able to reduce interleukin-6 (IL-6) cytokine production in whole human blood assay infected with Escherichia coli (Elisia et al, 2018), suggesting that the extracts may not just kill bacteria but also act as an anti-inflammatory agent in humans.…”
Section: Introductionmentioning
confidence: 99%
“…The alkaloidal fractions were separated from ethyl acetate extract using acid-base method 7 . The ethyl acetate extract-free alkaloid (13 g), was fractionated by VLC using gradient elution (n-hexane -ethyl acetate-methanol) 8 to give five significant fractions (A-E). Fraction C was sub-fractionated by radial chromatography using n-hexane -ethyl acetate (9:1.5, v/v) to give eight fractions (C1-C8).…”
Section: Extraction and Isolationmentioning
confidence: 99%